Study on the medium of propagation Morinda officinalis How by tissue culture - Phạm Thùy, Dung; Nguyễn Văn , Giáp; Vũ Thị, Mây; Phạm Thị, Mai Trang (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
Morinda officinalis How is a valuable medical plant in traditional medicine. The tuber of the Morinda officinalis How is widely used as a medicinal effect for tonic kidney, tonic kidney, strengthen tendons, increase resistance, toughness, reduce rheumatism. The extract of Morinda officinalis How has the effect of reducing blood pressure, quickly acting on the functional glands, improving the brain, helping to eat and sleep well (Li et al., 2003). To meet the source of high quality, bulk, it is necessary to have a fast, industrial-scale propagation method, so we have studied the medium of Morinda officinalis How propagating the plant by using the tissue culture method. The results of the study showed that: The suitable medium for the rapid multiplication of Morinda officnalis How was MS + 3.5 mg/l BAP + 0.2 mg/l IBA + 10 mg/l Riboflavin + 30 g/l sugar + 5 g/l agar, shoot factor multiplier reaches 10.14 times. The appropriate medium for rooting is 1/2MS + 0.3 mg/l IBA + 30 g/l sugar + 5 g/l agar + 0.4 g/l coal activated, rooting rate reached 100% and the average number of roots reached 3.44 roots / shoot. Survival rate at the nursery reached 95.20%.